The issue of checks by Vladivostok branch of State Bank in 1920 - A. L. Kiselev (Омский научный вестник: Серия "Общество. История. Современность")
The paper analyzes the issue of the Vladivostok branch of the State Bank of checks with a face value of 1000 rubles in January 1920, which became an attempt to replenish the stocks of banknotes to overcome the financial crisis that arose as a result of the Civil War and military intervention in the Russian Far East. The purpose of the work is to analyze known and, introducing into scientific circulation, identified historical sources that clarify and reveal certain issues when making a decision and organizing the issuance of checks by the Vladivostok branch of the State Bank. The theoretical basis of the study is a systematic approach and a comparative historical method. The author comes to the conclusion about the failure of issuance measures at the issuance stage, due to the intervention of counterfeiters. The failure of the checks increased the influence of foreign exchange in the region. The publication is addressed to researchers of financial policy during the Civil War and intervention in Russia.